Gümrük Birliği’nin öncesi ve sonrası ihracat ve ithalatın değişimi - Alemdar, Sibel (My University, 2011)
GÜMRÜK BİRLİĞİ’NİN ÖNCESİ VE SONRASI İHRACAT VE İTHALATIN DEĞİŞİMİ 1 Ocak 1996 tarihinde Türkiye ile Avrupa Birliği arasında Gümrük Birliği Anlaşması imzalanmıştır. Türkiye, Avrupa Birliği’ne tam üye olmadan Gümrük Birliği’ne giren tek ülkedir. Türkiye ile Avrupa Birliği arasındaki Gümrük Birliği; sanayi ürünlerini ve işlenmiş tarım ürünlerini kapsamaktadır. Bu anlaşma ile birlikte sanayi ürünleri ve işlenmiş tarım ürünleri ticaretinde gümrük vergileri kaldırılmıştır. Bu çalışmada Gümrük Birliği’nin Türkiye’nin dış ticaretine olan etkileri anlatılmaya çalışılmıştır. Gümrük Birliği’nin Türkiye’nin dış ticaret açığının artmasına neden olduğu görülmüştür.

CUSTOMS UNION’S BEFORE AND AFTER THE CHANGE OF EXPORTS AND IMPORTS On 1st of January 1996 Custom’s Union Agreement was signed between Turkey and the European Union. Turkey has been the only member of the Custom’s Union without being a fully member of the European Union. This Custom’s Union between Turkey and the European Union involves industrial products and agricultural products. With this agreement, the customs duties on trade in industrial goods and processed agricultural products have been removed. The effects of the Custom’s Union to the Turkey’s foreign trade was tried to explained in this study. It was monitored that the Turkey’s foreign trade defficit was increased cause of the Custom’s Union effects.
Keywords: Ekonomi; İhracat; İthalat; Uluslarası İktisat